RePIM in LOD: semantic technologies to manage, preserve, and disseminate knowledge about Italian secular music and lyric poetry from the 16th-17th centuries - Bonora, Paolo; Pompilio, Angelo (Umanistica Digitale, 2022)
The PIM in LOD project aimed to publish the "Repertorio della Poesia Italiana in Musica, 1500-1700" (RePIM) as Linked Open Data (LOD) dataset. For the extent and detail of its contents, RePIM is a reference archive for research on Italian secular music from the 16th-17th centuries. In recent years, scholars have been able to access it through a public web-based application. Due to the obsolescence of its information technology platform, the RePIM repository was set to be taken offline. To preserve this precious source, the project migrated its contents into a knowledge base (KB) adopting semantic technologies and designed an up-to-date end-user application. The paper illustrates the challenges of managing information about madrigal tradition and the digital knowledge preservation of bibliographic and philological information in the field of Italian secular music and lyric poetry of the 16th-17th centuries.